Environmental Assessment of Agricultural Activities on the Geochemistry of Surface Soils in the Pistachio Orchards of Southern Mehriz - J. Ghaneiardakani; S.A. Mazhari; F. Ayati (علوم آب و خاک, 2025)
This study investigates the impact of agricultural activities on the soils of southern Mehriz by analyzing their geochemical composition and comparing the physicochemical properties of pistachio orchard soils (agricultural soils) with those of undisturbed natural soils. The results indicate that agricultural practices have led to an increase in Total Organic Carbon (TOC), averaging 1.5%, and a reduction in soil acidity. Additionally, phosphorus concentrations have risen in agricultural soils. These soils also exhibit enrichment in elements such as cadmium (Cd), antimony (Sb), chromium (Cr), nickel (Ni), lead (Pb), scandium (Sc), and rare earth elements (REE) compared to natural soils, with a more homogenized REE distribution pattern. Although the concentrations of these trace elements remain within national environmental standards and below critical thresholds, the study highlights a significant increase in the bioavailability of heavy metals due to agricultural activity. This finding underscores a potential environmental risk if such changes are not properly managed in the future.